Heat Stress Regulates the Expression of Genes at Transcriptional and Post-Transcriptional Levels, Revealed by RNA-seq in Brachypodium distachyon - Chen, Shoukun; Li, Haifeng (Frontiers in Plant Science, 2017)
Heat stress greatly affects plant growth/development and influences the output of crops. With the increased occurrence of extreme high temperature, the negative influence on cereal products from heat stress becomes severer and severer. It is urgent to reveal the molecular mechanism in response to heat stress in plants. In this research, we used RNA-seq technology to identify differentially expressed genes (DEGs) in leaves of seedlings, leaves and inflorescences at heading stage of Brachypodium distachyon, one model plant of grasses. Results showed many genes in responding to heat stress. Of them, the expression level of 656 DEGs were altered in three groups of samples treated with high temperature. Gene ontology (GO) analysis showed that the highly enriched DEGs were responsible for heat stress and protein folding. According to KEGG pathway analysis, the DEGs were related mainly to photosynthesis-antenna proteins, the endoplasmic reticulum, and the spliceosome. Additionally, the expression level of 454 transcription factors belonging to 49 gene families was altered, as well as 1,973 splicing events occurred after treatment with high temperature. This research lays a foundation for characterizing the molecular mechanism of heat stress response and identifying key genes for those responses in plants. These findings also clearly show that heat stress regulates the expression of genes not only at transcriptional level, but also at post-transcriptional level.